The design of insurance coverage for medical products under imperfect competition (2015)
This paper studies the design of health insurance with ex post moral hazard, when there is imperfect competition in the market for the medical product. Various scenarios, such as monopoly pricing, price negotiation or horizontal differentiation are considered. The insurance contract specifies two types of copayments: an ad valorem coinsurance rate and a specific (per unit) copayment. By combining both copayment rates in an adequate way the insurer can effectively control the producer price, which is then set so that the producer's revenue just covers fixed costs. Consequently, a suitable regulation of the copayment instruments leads to the same reimbursement rule of individual expenditures as under perfect competition for medical products. Additional rationing of coverage because of imperfect competition as advocated by Feldstein (1973) is thus not necessary. Interestingly the optimal policy closely resembles a reference price mechanism in which copayment rates are low (possibly negative) and coinsurance rates are high.